Komparasi Respons ChatGPT dan Gemini terhadap Command Pattern Identik dengan Metode Black Box - Muchlis; Rusyda Maulida (LPPM STMIK ANTAR BANGSA, 2024)
This study aims to analyze the comparison between ChatGPT and Gemini using blackbox testing methods. The testing was conducted based on predefined rules to evaluate aspects such as answer accuracy, response speed, conversation context, and personalized responses. The results indicate that ChatGPT excels in terms of response quality and personalization, particularly in handling complex questions and maintaining conversation context. On the other hand, Gemini stands out in response efficiency but tends to provide more general answers. Overall, both chatbots have their respective strengths, and the choice between them can be adjusted based on user needs, prioritizing either speed or depth of response.